Glutathione-dependent phytohormone responses: Teasing apart signaling and antioxidant functions - Mhamdi, Amna (Landes Bioscience, 2013)
Cellular redox state is regulated by numerous components. The thiol-disulfide compound, glutathione, is considered to be one of the most significant, owing to its antioxidant power and potential influence over protein structure and function. While signaling roles for glutathione in plants have been suggested for several years, hard proof is scarce. Recently, through an approach based on genetic manipulation of glutathione in an oxidative stress background, we reported evidence that glutathione status is important to allow intracellular oxidation to activate pathogenesis-related phytohormone signaling pathways. This effect does not seem to be caused by changes in glutathione antioxidant capacity, and appears to be distinct to regulation through known players in pathogenesis responses, such as NPR1. Our data therefore suggest that new glutathione-dependent components that link oxidative stress to response outputs await discovery.